Changes in Whole Blood Gene Expression in Obese Subjects with Type 2 Diabetes Following Bariatric Surgery: a Pilot Study - Berisha, Stela Z.; Serre, David; Schauer, Philip; Kashyap, Sangeeta R.; Smith, Jonathan D. (PloS one, 2011)
A pilot study was performed in order to investigate the effects of bariatric surgery on whole blood gene expression profiles in obese subjects with type 2 diabetes. Whole blood from eleven obese subjects with type 2 diabetes was collected in PAXgene tubes prior to and 6-12 months after bariatric surgery. Total RNA was isolated, amplified, labeled and hybridized to Illumina gene expression microarrays. Clinical and expression data were analyzed using a paired t-test, and correlations between changes in clinical trait and transcript levels were calculated. Pathways were identified using Ingenuity Pathway Analysis and DAVID gene ontology software. Overall, bariatric surgery resulted in significant reduction of body mass index, fasting plasma glucose, fasting plasma insulin, and normalization of glycosylated hemoglobin levels. The expression levels of 204 transcripts, representing 200 unique genes, were significantly altered after bariatric surgery. Among the significantly regulated genes were GGT1, CAMP, DEFA1, LCN2, TP53, PDSS1, OLR1, CNTNAP5, DHCR24, HHAT and SARDH, which have been previously implicated in lipid metabolism, obesity and/or type 2 diabetes. Selected findings were replicated by quantitative real-time-PCR. The changes in expression of seven transcripts, WDR35, FLF45244, DHCR24, TIGD7, TOPBP1, TSHZ1, and FAM8A1 were strongly correlated with the changes in body weight, fasting plasma glucose and glycosylated hemoglobin content. The top pathways associated with gene expression changes after bariatric surgery was lipid metabolism, small molecule biochemistry and gene expression. Two antimicrobial peptides were among the transcripts with the largest changes in gene expression after bariatric surgery. Data from this pilot study suggest that whole blood expression levels of specific transcripts may be useful as biomarkers associated with susceptibility for type 2 diabetes and/or therapeutic response.